Effect of Cultural Norms and Traditional Beliefs on the Lived Experiences of Women in Agriculture in Rural Communities - Abasiama-Arit Aniche; Katherine McKee; Jackie Bruce (Journal of International Agricultural and Extension Education, 2025)
This study examined the effects of cultural norms and traditional beliefs on the lived experiences of women in agriculture in rural communities in Nigeria. Semi-structured interviews with rural Nigerian women and men yielded thematically examined qualitative data. The results revealed that cultural and traditional practices significantly impact the involvement, economic and social progress of women in agriculture in rural communities in Nigeria. Conservatism and patriarchy are central cultural norms and traditional beliefs in these communities. These norms and beliefs institutionalize discrimination against women, exclusion of women from decision-making, relegation of women to domestic duties, restriction of women's access to productive resources and economic opportunities, perpetuating their dependence on the menfolk, and subsistence farming. Women's groups act as a support system because they enable women to voice their concerns in various forums. The study recommends interventions that promote gender justice, education, and resource access to empower women and improve their livelihoods.
Keywords: cultural norms; traditional beliefs; rural women; lived experiences; decision-making/leadership